Generalized difference sequence spaces defined by Orlicz functions - Subramanian, N.; Altin, Y.; Bektas, Ç. (Aletheia University, 2007)
The idea of difference sequence spaces was introduced by Kizmaz [1] and then this subject has been studied and generalized by various mathematicians. In this paper we define some difference sequence spaces by Orlicz space of entire sequences and establish some inclusion relations. Some properties of these spaces are studied.
Keywords: Analytic sequence; Difference sequence; Entire sequence; Orlicz function